Evaluation of preference of interim cements used for provisional restorations in fixed dental prosthesis - a retrospective study - GOWTHAM, NEPPALA; AHMED, NABEEL (The journal of contemporary issues in business and government, 2020)
: Provisional or temporary cements play an important role in Fixed prosthodontics. There are numerous types of temporary cements, mainly used temporary materials are eugenol-based, non-eugenol based, and resin based. The aim of this retrospective cross-sectional study was to assess the preferred type of provisional cements used in temporization of fixed prosthesis. A cross- sectional, descriptive study was conducted in a university, on randomly selected individuals. The study group consists of adult patients who attended the outpatient Department of Prosthodontics from June 2019-March 2020. 86,000 case sheets were reviewed and sampling was done using simple random sampling. Descriptive analysis and chi square test is done in SPSS software version 23.0 by IBM to evaluate the correlation between age and profession with the type of provisional cement used. In 71.9% of the cases zinc oxide eugenol was prefered for temporary cementation. Association of graduation level and choice of temporary cement showed statistical significance(p - 0.00, p<0.05). We conclude that Zinc Oxide Eugenol was preferred for temporary cementation of provisional restorations, followed by Temp bond and IRM. Most of the postgraduates prefered IRM for temporary cementation of provisional restorations.